Interferences in the photoionization of water molecules - Martini, Lara (2019)
We study theoretically the photoionization of water molecules by monochromatic and linearly polarized radiation. The final state wavefunctions are given by Coulomb continuum wavefunctions and the water molecule bound states are represented using linear combinations of Slater type orbitals located on the centers of the molecule. We obtain total and differential cross sections. We compare them with more elaborated theoretical results and experiments obtaining a very good agreement in particular at enough high energies where there is a lack of predictions. We put in evidence three-center interference effects not only in the total cross sections but also we show that these effects may be detected in a direct way in the angular distributions of photoelectrons corresponding to randomly oriented molecules. In particular, we find that the interference effects under certain conditions may provoke a partial suppression of the emission of photoelectrons in the classical direction given by the polarization vector.